Entrepreneurial Strategies in Green and Sport Tourism to Enhance Revisit Intention in Mandalika MotoGP Circuit - Handaru, Agung Wahyu; Safariningsih, Ratna Tri Hari; Bahtar, Azlin Zanariah (Aptisi Transactions On Technopreneurship (ATT), 2025)
This study was conducted to develop a new model of revisit intention among tourists visiting a sport-tourism destination. The research took place in Mandalika, a tourist hotspot that successfully hosted the MotoGP event in Indonesia. To achieve this goal, 200 tourists in Mandalika participated by completing a questionnaire and interviews. Quantitative data analysis using Structural Equation Modeling (SEM) successfully developed a new revisit intention model influenced by green tourism, sports tourism, tourism infrastructure, and tourist experience. The contribution of all these elements to high revisit intention among tourists was recorded at 45.6%. The model also revealed that green tourism plays a significant role in shaping the tourist experience. Furthermore, the results showed that green tourism has the strongest influence in strengthening tourists' revisit intentions. The managerial implications derived from these findings suggest that, to increase revisit intentions, tourism stakeholders should actively promote eco-friendly and sports tourism, as these elements support sustainable practices and appeal to tourists seeking unique and environmentally conscious travel experiences.